Chapter 3 Derivation of Morality from Prudence - Arvan, Marcus (Routledge Focus on Philosophy, 2020)
This chapter derives and refines a novel normative moral theory and descriptive theory of moral psychology-Rightness as Fairness-from the theory of prudence defended in Chapter 2 of Neurofunctional Prudence and Morality: A Philosophical Theory. The chapter briefly summarizes Chapter 2's finding that prudent agents typically internalize 'moral risk-aversion'. The chapter then outlines how this prudential psychology leads prudent agents to want to know how to act in ways they will not regret in morally salient cases, as well as to regard moral actions as the only types of actions that satisfy this prudential interest. The chapter then uses these findings to defend a new derivation of Marcus Arvan's theory of morality, Rightness as Fairness, showing how the derivation successfully defends Rightness as Fairness against a variety of objections. Additionally, the chapter outlines how Arvan's theory of prudence can help substantiates the claim that Rightness as Fairness unifies a variety of competing moral frameworks: deontology, consequentialism, contractualism, and virtue ethics. Finally, the chapter shows how Chapter 2's theory of prudence entails some revisions to Rightness as Fairness, including the adoption of a series of Rawlsian original positions to settle prudential, moral, and social-political issues under ideal and nonideal circumstances.